Predictive factors for conversion to dementia in individuals with early‐onset mild cognitive impairment. (31st December 2021) - Baird, Kate; Baillon, Sarah; Lau, Lilian; Storey, Mathew; Lindesay, James; Velayudhan, Latha
Abstract: Background: Early‐onset Mild Cognitive Impairment (eoMCI) is defined as difficulties in cognition that are worse than in normal ageing for individuals below the age of 65. Some will go on to develop dementia, but there is currently limited research on which risk factors make someone more vulnerable to conversion. The present study aimed to examine whether sociodemographic and clinical factors at the initial presentation predict dementia progression in a cohort of eoMCI patients attending a memory service, at a university teaching hospital in the United Kingdom. Methods: A retrospective case note study utilising a database of individuals diagnosed with eoMCI between 2000‐2010 at a Younger Person's Memory Service (YPMS) in Leicestershire, England. Data collected at assessment included social factors, demographic characteristics, medical and psychiatric history, as well as standardised cognitive assessment scores. Results: Out of 531 subjects who attended YPMS between Jan 2000 to Dec 2010, 65 patients were diagnosed with eoMCI (47.7% female; age 56.4 years ±7.54). Of these, 21 individuals (32.3.%) converted to dementia during their course within the service. The mean period of conversion was 30.40 months (±23.08). A comparison between the subgroups revealed a significant association between dementia conversion and higher years of education, lower MMSE and CAMCOG (total and subscores) scores. A subsequent survival analysis found that higher education, lower CAMCOG score, impaired memory (remote, recent, learning) and impaired executive functions, at initial assessment were significant predictors for converting to dementia. Conclusion: Higher education, impaired memory and impaired executive functions at initial assessment are associated with a progression to a dementia diagnosis. The present naturalistic study identifies potential characteristics that predict the likelihood of an individual with eoMCI converting to any type of dementia. This has vital clinical implications and additional research is needed to explore these risk factors further.